ENGINEERING THE FUTURE OF GREEN ENERGY: AI-POWERED INTEGRATION FOR OPTIMAL RESOURCE MANAGEMENT - Shashank Reddy Beeravelly (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
Integrating artificial intelligence in renewable energy management represents a significant advancement in grid optimization and resource utilization. This article comprehensively analyzes a cloud-based system implementation that leverages real-time data integration and machine learning algorithms to optimize renewable energy distribution across multiple sources. The deployed system substantially improves energy distribution efficiency and resource utilization through predictive analytics and automated load balancing. By incorporating real-time weather pattern analysis and demand forecasting, the system achieved remarkable accuracy in energy output prediction, significantly outperforming traditional statistical methods. The implementation utilizes a novel deep-learning architecture that processes data from an extensive network of sensors across wind turbines and solar installations, managing high-volume data throughput in real-time. This article suggests that AI-driven integration systems can substantially improve the reliability and efficiency of renewable energy grids while reducing operational costs. This article provides crucial insights into the scalable implementation of intelligent energy management systems and their potential impact on the future of sustainable energy distribution. The results demonstrate that integrating advanced AI technologies with renewable energy infrastructure creates a more resilient, efficient, and sustainable power distribution network, setting a new standard for smart grid management and optimization.